Oral isotretinoin combined with oral terbinafine versus oral terbinafine alone to treat recurrent dermatophytosis: An open-label randomised clinical trial - Kaushal K Verma; Gridharan Senthilnathan; Saurabh Bhatia; Immaculata Xess; Vishal Gupta; Sada Nand Dwivedi; Kanika Sahni (Wolters Kluwer Medknow Publications, 2021)
Background: Recurrent dermatophytosis is becoming arduous to treat. Recently, oral itraconazole with oral isotretinoin was successful in a patient suffering from recurrent dermatophytosis. Objectives: To evaluate if oral isotretinoin confers any added benefit over oral terbinafine in the treatment of recurrent dermatophytosis. Materials and Methods: This was an open-label randomized clinical trial including 100 adult patients with recurrent tinea cruris and/or tinea corporis randomized into two groups; Group A (oral isotretinoin 0.5 mg/kg/day and oral terbinafine 250 mg twice daily) and Group B (oral terbinafine 250 mg twice daily) for 4 weeks, and followed up for 3 months. Fungal culture and antifungal susceptibility testing against terbinafine, fluconazole, amphotericin B, itraconazole, and griseofulvin were performed. Results: Out of the 100 patients, 91 patients (44 in Group A and 47 in Group B) completed the trial. Complete cure was seen in 19/44 (43.18%) patients in Group A and 20/47 (42.55%) patients in Group B (P = 0.951). Recurrence occurred in 12/19 (63.1%) patients in Group A and 13/20 (65%) patients in Group B (P = 0.904). Cheilitis and dryness of lips were the most common adverse effects seen in 32/44 (72.73%) patients in Group A. A total of 50 cultures were grown. The commonest species isolated was Trichophyton interdigitale in 36 (72%) patients, having a mean minimum inhibitory concentration of 3.13 μg/mL for terbinafine. However, for itraconazole, it was 0.13 μg/mL, and varied minimum inhibitory concentration (MIC) values were seen for fluconazole, griseofulvin, and amphotericin B. Conclusion: The addition of isotretinoin to terbinafine has no added benefit in treating patients with recurrent dermatophytosis.